Employees Perception of Human Capital Practices, Employee's Productivity, and Company Performance - Audy Thuda; Junita Sari; Anita Maharani (Integrated Journal of Business and Economics (IJBE), 2019)
This study aims to find out whether there is an influence between human capital practices and productivity on company performance. The theoretical approach raised in this study is about human capital, productivity, and company performance. The research method approach carried out in this study is quantitative, namely by regression testing, and previously testing the quality of the instrument through validity and reliability tests. The results obtained are that the practice of human capital and productivity does affect the performance of the company. So it is recommended that companies that are the samples of this study can consider policies that can support company performance through the practice of human capital and support for employee productivity, although there are still many other factors that affect company performance.